International environmental law in the Arctic : a dawn for new international legal environmental instruments for the Arctic? - Ateawung, Rene (fi=Lapin yliopisto|en=University of Lapland|, 2018)
This article addresses the state of international environmental law (IEL) in the Arctic. The focus is on the ongoing legal mechanisms put in place for the maintenance of IEL in the various Arctic States. From the onset, climate change has drastic legal effects on the Arctic States. The consequences have led to changes in the environmental politics of the Arctic States. The soft law approach that has traditionally been applied for several decades sometimes conflicts with the principle of State sovereignty. A few provisions of the UNCLOS and other related international instruments are ambiguous. There is no exclusive IEL treaty involving all the Arctic States. The requirement of one as it is the case with the Antarctic Treaty System in the polar seems apparent. The preparation of a new one and/or other related international legal environmental instruments for the future Arctic region is highly recommended.